ANALISIS KUALITAS PELAYANAN AIR MINUM DI KANTOR PDAM CABANG SEMARANG TIMUR - Harmoko, Fatmala Resti; Warsono, Hardi; Rengga, Aloysius (Journal of Public Policy and Management Review, 2013)
Current public service reforms are needed to deal with the demands of the public to public services is increasing. Society not only questioned whether or not fulfilled the need for services and public services, but has questioned the quality of public services that are recording received from the government. Changing demands for improved public services are addressed to government officials, regarding public services provided to citizens. The poor quality of public services provided to government employees into bad image in the community. The low quality of service in East Semarang PDAM indication of the number of customers who made complaints to various problems such as leaking pipes, running water and a little murky, opaque and meter the rate mismatch between the amount of water used. The purpose of this study was to determine the condition of existing service quality in East Semarang PDAM. This research is a quantitative description of the 5 inidikator ie tangible (direct evidence) reliability (reliability), responsiveness (responsiveness), access (ease) and courtessy (employee attitudes). The sample in this research that drinking water service users in East Semarang PDAM by 53 respondents. Collection of data by distributing questionnaires then the data were analyzed by using quantitative descriptive analysis using the mean (average). Research findings indicate that although the quality of service in East Semarang PDAM less well, but in general the quality of service was good, although there are the indicators that are less good as inidkator responsiveness and access.